UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENERAPKAN STRATEGI PEMBELAJARAN "THINK-TALK-WRITE" SEBAGAI ALTERNATIF PEMECAHAN MASALAH MATEMATIKA PADA WILAYAH SMA BINAAN DI KABUPATEN DOMPU MELALUI SUPERVISI KOLABORATIF - Suaidin (Aksioma, 2014)
Abstract: This study is based on the low achievement in mathematics in five high schools. It appens because students do not achieve mastery learning as seen from the results of tests, whereas mathematics is a main lesson on all levels. Contributing factors in the process of learning are students sometimes lack of the motivation to learn, low-absorption students, do not understand what is delivered by teachers, and poor teacher performance. These problems can be solved by collaborative supervision in carrying out the management of teaching from planning, implementation of teaching and learning, and evaluation. The purpose of this study is to increase in teachers in implementing the strategy of Think-Talk-Write which will have implications on the increase in student learning outcomes in mathematics subjects, special on aspects of communication skills and problem solving at the level of think commonly found on Achievement Indicators at least competence in curriculum KTSP 2006. The method of this research is to study the action (action research) with a collaborative approach undertaken by two cycles. Based on the results of action research can be concluded: (1) supervision of an individual with a collaborative approach to give effect to increase the performance of high school mathematics teacher in the target area in the district of Dompu both components or learning plan implementation component of learning by using Think-Talk-Write, and (2) increasing the impact on teacher performance improving mathematics learning outcomes of students. Keywords: collaborative supervision, mathematical problem solving, Think- Talk-Write.